Lesbian and gay teachers and sex/uality education policy enactment in schools. Issue 6 (2nd November 2018) - Rudoe, Naomi
ABSTRACT: This paper examines lesbian and gay teachers' identities and experiences in schools in the context of school policies relating to homophobia and to sex and sexuality education. Drawing on semi-structured interviews with 12 lesbian and gay teachers working in English and Welsh schools, and using the concept of 'policy enactment', I analyse the ways in which school policies around homo/bi/transphobic bullying and sex/uality education and their enactment are perceived by lesbian and gay teachers. The article examines teachers' personal experiences in relation to sexuality in school, and then broadens out into related issues for pupils and a discussion of the varied approaches to sex and relationships education in the schools. I argue that the enactment of these policies is not straightforward, and that they could be better supported by a more inclusive and comprehensive sexuality education curriculum.